Isotopic Scintigraphy in Intrathecal Drug Delivery Failure: A Single‐Institution Case Series. Issue 7 (18th September 2020) - Delhaas, Elmar M.; van Assema, Daniëlle M.E.; Fröberg, Alida C.; Zwezerijnen, Ben G.J.C.; Harhangi, Biswadjiet S.; Frankema, Sander P.G.; Huygen, Frank J.P.M.; van der Lugt, Aad
Abstract: Background: The aim of this study was to assess the feasibility and diagnostic accuracy of an optimized 111 Indium‐diethylenetriamine‐penta‐acetic‐acid single‐photon‐emission computed tomography (CT) ( 111 In‐DTPA SPECT‐CT) examination in patients with suspected intrathecal drug delivery (ITDD) failure. Materials and Methods: Retrospective analysis of routinely collected observational data from a case series of patients in the setting of the academic Center for Pain Medicine, Departments of Radiology and Nuclear Medicine and Neurosurgery. Twenty‐seven patients participated between January 2014 and January 2019. Thirty‐six optimized examinations including standardized pump flow rate with additional SPECT‐CT imaging and a stepwise standardized analysis were performed. A 10 mL mixture of medication and 20 MBq 111In‐DTPA was injected into the pump reservoir. Planar and SPECT‐CT images were acquired at 24, 48, and 72 hours (h) after injection and at 96 hours and/or seven days, if needed. All images were reassessed by the first two authors using an optimized procedure. Results and Conclusions: Twenty‐two abnormalities were identified in 21 examinations, with these abnormalities consisting of leakage ( n = 7), spinal catheter obstruction ( n = 7), and cerebrospinal fluid flow obstruction ( n = 8). Interventions ( n = 19) confirmed the cause of ITDD failure. A false‐positive finding at follow‐up ( n = 1) and a false‐negative finding ( n = 1) were encountered. Sensitivity was 95% (20/21) and the specificity 93% (14/15). A significant difference ( p < 0.001) was found between the accuracy of the conventical and the optimized analysis. The optimized 111 In‐DTPA SPECT‐CT examination is a powerful diagnostic tool for detecting the cause of ITDD failure.